ANTIHEROES-PRODIGE: Quantifying the connection from the envelope to the disk with the IRAM 30 m telescope and NOEMA: I. Infalling streamers in L1448N - Gieser, Caroline; Caselli, P.; Segura-Cox, D. M.; Pineda, J. E.; Busch, L. A.; Valdivia-Mena, M. T.; Maureira, M. J.; Lin, Y.; Hsieh, T. H.; Chou, Y. R.; Bouscasse, L.; Cortés, P. C.; et al. (Astronomy and astrophysics, 2025)
Context: Star formation is a hierarchical process that ranges from molecular clouds to individual protostars. In particular, it remains to be understood how infalling asymmetric structures (streamers) that deliver new material to protostellar systems are connected to the surrounding envelope. Aims: We investigated the connection between the cloud material at scales of 10 000-300 au toward L1448N in the Perseus starforming region, which hosts three young Class 0/I protostellar systems (IRS3A, IRS3B, and IRS3C). Methods: Sensitive molecular line observations taken with the Institut de Radioastronomie Millimetrique (IRAM) 30 m telescope and the Northern Extended Millimeter Array (NOEMA) at 1.4 mm were used to study the kinematic properties in the region that is traced by the molecular lines (C18O, SO, DCN, and SO2). The temperature in the region was estimated using transitions of c-C3H2. Results: Several infalling streamers are associated with the protostellar systems. Some of them are traced by C18O and DCN, and one of them is bright in SO and SO2. The kinematic properties of the former streamers are consistent with the velocities observed at large envelope scales of 10 000 au, while the kinematics of the latter case are different. The masses and infall rates of the streamers are 0.01 M⊙ and 0.01-0.1 M⊙ and 106 M⊙ yr-1 and 5-18 × 106 M⊙ yr-1 for IRS3A and IRS3C. The envelope mass in the L1448N region is ≈16 M⊙, and the mass of a single streamer is thus lower than the envelope mass (<1%). Compared to the estimated mass of the protostellar systems, however, a single streamer could deliver up to 1 and 8-17% of mass toward IRS3A (M* ≈ 1.2 M⊙) and IRS3C (M* ≈ 1 M⊙), respectively. Conclusions: The rotational signatures of structures in L1448N are all connected, from the large-scale envelope and infalling streamers to the rotation of all three disks. Two of the three Class 0/I protostellar systems are still fed by this surrounding material, which can be associated with the remnant envelope. We also found a streamer that is bright in SO and SO2 toward IRS3C. This might be connected to a nearby sulfur reservoir. Further studies are required to study the diverse chemical compositions and the origin of the streamers.
Gesehen am 18.02.2026